Модель управління розвитком поліграфічних підприємств - Гуткевич, Світлана Олександрівна; Шендерівська, Ліна Петрівна (My University, 2015)
Визначена концепція розвитку підприємств поліграфічної промисловості, що враховує особливості діяльності поліграфічних підприємств, сучасні умови їх функціонування. На основі концепції розвитку розроблена модель управління розвитком поліграфічних підприємств. Обґрунтовані перспективні напрями розвитку підприємств та визначено їх вплив на показники розвитку підприємств. The concepts of enterprise printing industry, taking into account the features of printing companies, current conditions of their operation is grounded The conditions of macro- and micro levels of management, that lead to the deterioration of printing companies are determined. The conditions of globalization, informatization, high intensity innovation, that promote the development of printing companies are discovered. The opportunities of development of printing enterprises, such as, the European integration process and availability of production capacity, reduce the costs of innovative technologies of printing production are identified. The new tasks of development of enterprises accordingly to the necessity of reorientation of tasks in conditions of modern economy are given. The reasonable conditions and principles to be followed to perform tasks, such as balancing interests – economic, social, environmental; fostering innovation enterprises; lifelong learning as a trend of improving the quality of education; quality standards implementation, the need for government support and regulation of publishing and printing companies, integration of publishing and printing industries and other are grounded. The model of management of printing enterprises based on the concept of development is proposed. The improvement of cooperation between the objects of publishing and the printing complex by creation of associations is proposed. Necessity of diversification and directions of improvement in the management in new conditions is justified. Increase of investment through the use of profit as the main source of development is recommended. Expediency of management of development of enterprises on the model is justified.
Keywords: управління; розвиток; модель; концепція; ефективність; поліграфічне підприємство; management; development; model; concept; efficiency; printing enterprise; кафедра міжнародної економіки